REIMBURSEMENT OF FUNERAL COSTS IN ROMAN LAW - Stanojlović, Vukašin (Zbornik radova Pravnog fakulteta u Novom Sadu, 2023)
The sacred and moral duty of family members, primarily heirs, was to bury the deceased. The funeral ceremony and the size of the funeral monument reflected the social status of the decedent; nonetheless the funeral itself had a dual role – to ensure a peaceful transition of the soul into eternity and to provide peace for the descendants. Reading the legal texts, it could easily be seen that the issue of funeral costs was at the high level of importance for the offspring. In addition, we can assert that the Roman legislators, lawyers and priests were particular aware of its importance. In this regard, the praetor issued the Edictum de sumptibus funerum, establishing the actio funeraria, in order to determine who and under what conditions acquires the right of reimbursement of funeral costs, but also to ensure that no one is buried at someone else's expense. The aim of this paper is to answer the questions who had the liability and responsibility to organize the funeral and bear it costs, when and under what conditions could organizer sue for the incurred expense and what was considered as the funeral cost.Results indicate the following. The grandeur of the funeral and the amount of funeral expenses depended on the social status and wealth of the deceased. The costs of the funeral were divided into necessary, which cover expenses in the name of activities without funeral could not take place and convenient, which depend on the reputation of the defunctus. Although there have been attempts to expand Ulpian's classification into necessary and convenient expenses, this does not seem to have been the case at the outset. Funeral expenses were mostly – with a few exceptions, covered from the inheritance, and the obligation to reimburse the costs incurred was most often borne by the persons burying the deceased. From Cicero's and Ulpian's texts, we learn which persons were obliged to bury the deceased, i.e. cover funeral expenses. It is important to note that research shows that from the moment of death until the costs are paid, the inheritance is in the regime of hereditas iacens, and that it is administered by the praetor to ensure that no one is buried at someone else's expense.The paper uses linguistic, historical and systematic interpretation of passages D.11.7.12.4–6, D.11.7.13, D.11.7.14.3,4,6 and 10, D.11.7.21, Cic.Leg.2.48–49, as well as historical method.
Keywords: Death in Ancient Rome. – Roman Funeral. – Funeral Costs. – Cicero. – Ulpianus.